Autonomy and decentralization in the global imperial crisis: the Russian Empire and the Soviet Union in 1905-1924 - Sablin, Ivan; Semenov, Aleksandr (Modern intellectual history, 2018)
This article brings the case of imperial transformation of the Russian Empire/Soviet Union into global discussions about empire, nationalism, and postimperial governance, and highlights the political and legal imaginaries that shaped this transformation, including their global and entangled character. This article argues that the legal and political discourses of decentralization, autonomism, and federalism that circulated at the time of the imperial crisis between the Revolution of 1905 and the adoption of the Soviet Constitution in 1924 contributed to the formation of an ethno-national federation in place of the Russian Empire, despite both the efforts of the Bolsheviks to create a unitary state, and the expectations of a different future among contemporary observers. At the same time, the postimperial institutional framework became a product of political conjunctures rather than the legal discourse. Its weakness before the consolidating party dictatorship made the Soviet Union a showcase of sham federalism and autonomism.
Gesehen am 27.05.2019